Stochastic modeling : a thorough guide to evaluate, pre-process, model and compare time series with MATLAB software /: a thorough guide to evaluate, pre-process, model and compare time series with MATLAB software. (2022) - Bonakdari, Hossein; Zeynoddin, Mohammad
No abstract available